Risk factors for community-associated Clostridioides difficile infection in young children. (2019) - Weng, M. K.; Adkins, S. H.; Bamberg, W.; Farley, M. M.; Espinosa, C. C.; Wilson, L.; Perlmutter, R.; Holzbauer, S.; Whitten, T.; Phipps, E. C.; Hancock, E. B.; Dumyati, G.; et al.
Abstract: The majority of paediatric Clostridioides difficile infections (CDI) are community-associated (CA), but few data exist regarding associated risk factors. We conducted a case–control study to evaluate CA-CDI risk factors in young children. Participants were enrolled from eight US sites during October 2014–February 2016. Case-patients were defined as children aged 1–5 years with a positive C. difficile specimen collected as an outpatient or ⩽3 days of hospital admission, who had no healthcare facility admission in the prior 12 weeks and no history of CDI. Each case-patient was matched to one control. Caregivers were interviewed regarding relevant exposures. Multivariable conditional logistic regression was performed. Of 68 pairs, 44.1% were female. More case-patients than controls had a comorbidity (33.3% vs. 12.1%; P = 0.01); recent higher-risk outpatient exposures (34.9% vs. 17.7%; P = 0.03); recent antibiotic use (54.4% vs. 19.4%; P < 0.0001); or recent exposure to a household member with diarrhoea (41.3% vs. 21.5%; P = 0.04). In multivariable analysis, antibiotic exposure in the preceding 12 weeks was significantly associated with CA-CDI (adjusted matched odds ratio, 6.25; 95% CI 2.18–17.96). Improved antibiotic prescribing might reduce CA-CDI in this population. Further evaluation of the potential role of outpatient healthcare and household exposures in C. difficile transmission is needed.